The Effectiveness of Practical Training in Social Work on Improving the Skills of University Students - Al-Raggad, Fatima Eed; Alsabeelah, Amal Metleb (Journal of Ecohumanism, 2024)
The purpose of this research was to determine whether or not social work students' communication, problem-solving, critical-thinking, teamwork, and professional abilities were enhanced by practical training. Additionally, it aimed to compare these abilities across students at Jordan's Al-Zaytoonah University and those at Al-Balqa Applied University. One hundred twenty male and female students from two Jordanian universities—Al-Zaytoonah and Al-Balqa Applied University—made up the study's sample. Mathematical means and standard deviations were utilized to analyze the findings of a questionnaire that assessed the various skills. The results demonstrated that students at Al-Zaytoonah University of Jordan had better practical communication skills on average, with an average score of 4.567 (±0.398) on the "Communicating Clearly" ability test, compared to 4.123 (±0.462) at Al-Balqa Applied University. The average score for problem-solving strategies applied by students at Al-Zaytoonah University was 4.678 (±0.481), whereas the average score for students at Al-Balqa University was 4.234 (±0.532). In the paragraph "Working effectively within teams," students from Al-Zaytoonah University had an average score of 4.567 (±0.463) while students from Al-Balqa University had an average score of 4.123 (±0.484). As for professional skills, the results demonstrated that students at Al-Zaytoonah University outperformed their counterparts at Al-Balqa Applied University. The former had an average skill of "Applying academic knowledge" of 4.567 (±0.420), while the latter had 4.123 (±0.472).